Clinical and Genetic Description of Hereditary Chronic Pancreatitis in Pakistani Children - Cheema, Huma Arshad; Fayyaz, Zafar; Saeed, Anjum; Anjum, Muhammad Nadeem; Ijaz, Sadaqat; Alvi, Muhammad Arshad; Batool, Syeda Sara (Turkish Journal of Gastroenterology, 2023)
Background/Aims: The purpose of this study was to identify the spectrum and frequency of pathogenic variants as well as the clinical and genetic insight of hereditary chronic pancreatitis in Pakistani children. Materials and Methods: The deoxyribonucleic acid of affected probands of 44 unrelated Pakistani families, having hereditary chronic pancreatitis-affected children, were subjected to massive parallel sequencing for candidate reported genes (SPINK1, PRSS1, CFTR, CPA1, CTRC, CBS, AGL, PHKB, and LPL). Data were analyzed using different bioinformatics tools for the variants and in-silico analysis. All the identified variants were validated by direct sequencing of the targeted exons in the probands and their parents. Results: There were 50 patients included in this study with confirmed hereditary chronic pancreatitis. Nine known mutations in SPINK1, PRSS1, CFTR, CTRC, CBS, and AGL genes, and 10 novel variants in LPL, CFTR, CTR, and PHKB genes were identified. The identified variants were found in heterozygous, compound heterozygous, and trans-heterozygous forms, with rare allele frequency in the normal population. The novel variants were [c.378C>T(p.Lys126Asn) and c.719G>A(p.Arg240Gln) in CTRC, c.586-3C>A and c.763A>G(p.Arg255Gly) in CPA1, c.1160_1161insT(p.Lys387Asnfs*26), c.784C>T(p.Gln262*), c.1139+1G>A, c.175G>A(p.Gly59Arg) in LPL, c.388C>G(p.leu130val) in CFTR, and c.2327G>A(p.Arg776His in PHKB)]. The phenotypic characteristics were variable and correlated with the relevant variant. Conclusions: The genetic composition plays a significant role in the predisposition of hereditary chronic pancreatitis. The clinical presentation varies with the genetic determinant involved. This information would help in building up a diagnostic algorithm for our population that can be used for genetic screening services in affected cohorts.